Fine-mapping of a QTL and identification of candidate genes associated with the lateral branch angle of peanuts (Arachis hypogaea L.) on chromosome B05 - Deng, Hongtao; Li, Xiukun; Cui, Shunli; Li, Li; Meng, Qinglin; Shang, Yanxia; Liu, Yingru; Hou, Mingyu; Liu, Lifeng (Frontiers in Plant Science, 2024)
Peanuts play a crucial role as an oil crop, serving not only as a primary source of edible oil but also offering ample protein and vitamins for human consumption. The lateral branch angle of peanuts is the angle between the main stem and the first pair of lateral branches, which is an important agronomic trait of peanuts, significantly impacts the peg penetration into the soil, plant growth, and pod yield. It is closely intertwined with planting density, cultivation techniques, and mechanized harvesting methods. Therefore, the lateral branch angle holds substantial importance in enhancing peanut yield and facilitating mechanization. In order to conduct in-depth research on the lateral branch angle of peanuts, this research is grounded in the QTL mapping findings, specifically focusing on the QTL qGH associated with the lateral branch angle of peanuts located on chromosome B05 (142610834-146688220). By using Jihua 5 and PZ42 for backcrossing, a BC1F2 population comprising 8000 individual plants was established.Molecular markers were then developed to screen the offspring plants, recombine individual plants, conduct fine mapping. he results showed that using the phenotype and genotype of 464 recombinant individual plants selected from 8000 offspring, narrow down the localization interval to 48kb, and designate it as qLBA. The gene Arahy.C4FM6Y, responsible for the F-Box protein, was identified within qLBA through screening. Real-time quantitative detection of Arahy.C4FM6Y was carried out using M130 and Jihua 5, revealing that the expression level of Arahy.C4FM6Y at the junction of the main stem and the first lateral branch of peanuts was lower in M130 compared to Jihua 5 during the growth period of the first lateral branch from 1 to 10 centimeters. Consequently, Arahy.C4FM6Y emerges as a gene that restrains the increase in the angle of the first lateral branch in peanuts. This investigation offers novel genetic reservoirs for peanut plant type breeding and furnishes a theoretical foundation for molecular marker-assisted peanut breeding.